Development and Environment (Springer International Publishing, 2018)
Rather than a loosely connected list of facts/topics, this book addresses virtually every field that involves the use of developing animals in environmental science. In doing so, it will help define the scientific collective within these fields to both those readers who are "outside" of a particular field (students and professionals alike) and those who work within said field, where multiple iterations of the same job description exist. Both the content and choice of authors fully support this goal, as the editors and contributing authors represent contemporary thought and experimentation in their respective fields - ranging from developmental physiology through environmental toxicology to medicine. As such, this work will appeal to a broad audience, including any scientist or trainee interested in the nexus of environment, development and physiology.